Composite aerogel for adsorbing Cs < + > and Sr < 2 + > in water and preparation method thereof

By synthesizing KMg@ZIF-8/MoS2@SA aerogel, the growth characteristics of SA carrier and ZIF-8, combined with the selective adsorption properties of potassium ferrocyanide magnesium, the problems of low Cs+ and Sr2+ removal capacity and slow rate in wastewater were solved, and efficient Cs and Sr ion purification was achieved.

CN119897075AActive Publication Date: 2025-04-29CHANGZHOU UNIV
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202510120096.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-25
Publication Date
2025-04-29
Estimated Expiration
2045-01-25

AI Technical Summary

Technical Problem

The prior art has problems with low removal capacity and slow removal rate when removing Cs+ and Sr2+ in wastewater, making it difficult to effectively deal with these radioactive elements, resulting in environmental pollution and health risks.

Method used

By synthesizing MoS2@SA aerogel and growing ZIF-8 and potassium ferrocyanide through surface circulating, KMg@ZIF-8/MoS2@SA aerogel was obtained, which was used to adsorb Cs+ and Sr2+ in water. This method uses SA as a carrier, loaded with molybdenum disulfide, and grows ZIF-8, and finally the surface grows potassium ferrocyanide with selective adsorption properties for Cs+ and Sr2+ to achieve efficient adsorption.

Benefits of technology

When KMg@ZIF-8/MoS2@SA aerogel adsorbs Cs+ and Sr2+ in wastewater, the removal rates reach 98.9% and 99.8%, respectively, which significantly improves the removal capacity and removal rate, and achieves efficient purification of Cs and Sr ions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119897075A_ABST
    Figure CN119897075A_ABST
Patent Text Reader

Abstract

The invention discloses composite aerogel for adsorbing Cs < + > and Sr < 2 + > in wastewater and a preparation method of the composite aerogel. The preparation method comprises the following steps: mixing molybdenum disulfide (MoS2) nanosheets with sodium alginate (SA), crosslinking with calcium chloride, and freeze-drying to obtain MoS2-SA aerogel; sequentially putting the MoS < 2 >-SA aerogel into a solution containing zinc acetate dihydrate and 2-methylimidazole to soak and cyclically grow ZIF-8, so as to obtain ZIF-8 / MoS < 2 >-SA aerogel; the ZIF-8 / MoS2-coated SA aerogel is sequentially put into a solution containing potassium ferrocyanide and magnesium chloride to be soaked to grow potassium magnesium ferrohydride, and the KMg-coated ZIF-8 / MoS2-coated SA aerogel is obtained. The composite aerogel can effectively adsorb heavy metal ions Cs and Sr in water, and is widely applied to the treatment process of wastewater discharged from heavy metal ion research institutes, factories and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of water treatment adsorption materials, and specifically relates to a method for adsorbing Cs in wastewater. + , Sr 2+ A method for preparing a composite aerogel, Background Art

[0002] With the rapid increase in population and the rapid development of industry, global energy demand has shown explosive growth. Nuclear power has become one of the most important resources to cope with energy shortages. However, nuclear energy safety has always been a challenging issue. Although the discharged nuclear wastewater has been treated, according to the report of the International Atomic Energy Agency, 10 radioactive isotopes ( 3 H. 14 C. 134 Cs, 137 Cs, 60 Co. 125 Sb, 106 Such as 90 Sr. 99 Tc, 129 I). Among these radionuclides, 137 Cs and 90 Sr is one of the most harmful radioactive elements, causing serious pollution and damage to the environment and threatening human life. 137 Cs and 90 The half-lives of Sr are both very long, 30.12 years and 28.79 years respectively, which will damage the environment over a long period of time. 137 Cs is usually expressed as Cs + exists in the form of 90 Sr is usually expressed as Sr 2+ It exists in the form of ions, which can quickly migrate into the food chain due to its high water solubility and high environmental mobility. + With K + 、Na + have similar chemical properties, and Sr 2+ With Ca 2+ Because they have similar chemical properties, they can be easily assimilated by terrestrial and aquatic organisms and then enter the human food chain, where they are easily absorbed by the body, causing cell damage or death and soft tissue cancers, such as thyroid cancer. Therefore, it is necessary to develop effective methods to remove them from aqueous nuclear waste. 137 Cs and 90 Sr. is crucial.

[0003] Molybdenum disulfide (MoS2) is a graphene-like two-dimensional transition metal sulfide with a unique three-layer stacked atomic layer (S-Mo-S) sandwich structure and excellent chemical stability and structural designability. In addition, the rich sulfur groups on the surface and edges of MoS2 give it good adsorption properties for heavy metal elements. Therefore, in recent years, MoS2 has become an ideal material for adsorption and reduction removal of heavy metal elements in wastewater. + The capacity of Cs2 has been greatly improved by researchers at home and abroad. However, these composite modified nano-MoS2 can effectively treat Cs2 + There are also disadvantages such as low removal capacity and slow removal rate. Therefore, how to improve the treatment of Cs by MoS2? + The removal capacity and removal rate remain extremely challenging research topics in the field of heavy metal wastewater pollution.

[0004] 2-Methylimidazole zinc salt ZIF-8 is composed of metal ions (Zn 2+ ) and an organic ligand (2-methylimidazole), and was first designed, synthesized and reported by the research group of Academician Chen Xiaoming of Sun Yat-sen University. ZIF-8 is the most thoroughly studied ZIFs material and the most widely used ZIFs material. In the crystal structure of ZIF-8, polyhedrons represent Zn, spheres represent N, and lines represent C. It has a sod-type topological structure and is composed of 1.16 nm nanocages connected by six-element windows with a size of 0.34 nm. ZIF-8 has many characteristics such as high thermal stability, high chemical stability, high controllability, high pore volume, and high hydrophobicity, and is widely used in many fields.

[0005] Metal ferrocyanide mainly refers to transition metal (Fe, Co, Ni, Cu, Zn) ferrocyanide, the chemical formula is A a M b [Fe(CN)6] c , where A represents monovalent cations such as Cs and K, and M represents transition metal ions. Metal ferrocyanide is a class of substances with an octahedral central cubic structure, in which metal iron ions are connected by CΞN bonds and alternately form a three-dimensional network aggregate structure at the nodes of the central cubic lattice. Monovalent cations fill the gaps in the cubic lattice to provide charge compensation. Ferrocyanide has zeolite properties and can react with K in aqueous solution. + 、Na + Plasma exchange is fast, and the affinity for metal ions is: Cs + >Rb + >NH 4+ >K + >Na + >Li + Based on this, ferrocyanide is often used as an ion exchanger to treat Cs-containing+ In addition, the transition metals in ferrocyanide are usually nickel, cobalt, copper and zinc, and their use tends to increase production costs. For this problem, choosing cheap metals to replace these transition metals is often the best solution. Summary of the invention

[0006] The present invention aims to provide a method for adsorbing Cs in wastewater. + , Sr 2+ Composite aerogel and preparation method thereof. The present invention first synthesizes MoS2@SA aerogel, and then cyclically grows ZIF-8 and potassium magnesium ferrocyanide on the surface to obtain KMg@ZIF-8 / MoS2@SA aerogel, which is used to adsorb metal ions Cs and Sr in water and has broad application prospects.

[0007] The present invention first provides a method for adsorbing Cs in water. + , Sr 2+ The preparation method of the composite aerogel comprises the following steps: (1) The MoS2 dispersion and the sodium alginate (SA) solution are mixed evenly to obtain a mixed solution, the mixed solution is freeze-dried and then taken out, a calcium chloride solution is added for cross-linking reaction, and the MoS2@SA aerogel is obtained after washing and drying; (2) The MoS2@SA aerogel is sequentially immersed in a soluble zinc salt aqueous solution and a 2-methylimidazole aqueous solution for a growth cycle, and then freeze-dried; after being taken out, the growth cycle is repeated to obtain ZIF-8 / MoS2@SA aerogel; Specifically, the MoS2@SA aerogel is first immersed in a soluble zinc salt aqueous solution for 3 to 6 hours, and then immersed in a 2-methylimidazole aqueous solution for 3 to 6 hours, and a growth cycle is performed. The aerogel that has grown ZIF-8 once is taken out and the above steps are repeated, and the ZIF-8 / MoS2@SA aerogel is freeze-dried for 24 to 72 hours to obtain the ZIF-8 / MoS2@SA aerogel. The growth steps are three times in total, and the cycle time is 6 to 12 hours. The MoS2@SA aerogel fully reacts in the soluble zinc salt and 2-methylimidazole solution to generate small spherical particles with smooth surfaces and clear boundaries. In practical applications, the Zn-O in ZIF-8 is broken to achieve Zn 2+ Choose to exchange Sr 2+ Selective adsorption effect.

[0008] (3) The ZIF-8 / MoS2@SA aerogel was immersed in an aqueous solution of potassium ferrocyanide and an aqueous solution of magnesium chloride in turn and freeze-dried to obtain an aerogel loaded with potassium ferrocyanide and magnesium, which was labeled as KMg@ZIF-8 / MoS2@SA aerogel.

[0009] Specifically, the ZIF-8 / MoS2@SA aerogel is first immersed in a potassium ferrocyanide aqueous solution for 3 to 6 hours, and then immersed in a magnesium chloride aqueous solution for 3 to 6 hours for growth. The product is taken out, washed with pure water, and freeze-dried for 24 to 72 hours, so that potassium and magnesium ferrocyanide grow uniformly on the surface of the ZIF-8 / MoS2@SA aerogel.

[0010] In the above technical solution, preferably, the mass ratio of MoS2 and SA is 1:1, and the concentration of sodium alginate in the mixed solution is 5~10 mg / mL.

[0011] Preferably, the MoS2 dispersion and SA solution in step (1) are mixed by stirring first and then ultrasonic mixing at a temperature of 30-50 °C, a rotation speed of 300-500 r / min, and a mixing time of 0.5-2 h. Preferably, the concentration of the calcium chloride solution in step (1) is 0.1-1 mol / L.

[0012] Preferably, the MoS2 described in step (1) is MoS2 nanosheets, which are prepared by the following method: dissolving or dispersing ammonium molybdate and thiourea in water, stirring and mixing evenly, hydrothermally reacting at 180-220°C for 24-48 hours, naturally cooling to room temperature, washing with deionized water and ethanol, and freeze-drying to obtain MoS2 nanosheets; wherein the molar ratio of thiourea in molybdenum ions of ammonium molybdate is 1:4-5.

[0013] Preferably, the freeze-drying temperature in step (1) is -50 to -60°C, and the freezing time is 24 to 72 hours.

[0014] Preferably, the molar ratio of the soluble zinc salt to 2-methylimidazole in step (2) is 1:8-9; the concentration of the soluble zinc salt aqueous solution is 0.09-0.1 mol / L; and the volume ratio of the soluble zinc salt aqueous solution to the 2-methylimidazole aqueous solution is 1:1.

[0015] Preferably, the immersion time in step (2) is 3 to 6 hours; and the total number of repeated growth cycles is more than three times.

[0016] Preferably, the concentration of the potassium ferrocyanide aqueous solution in step (3) is 0.5-1.5 mol / L; the concentration of the magnesium chloride aqueous solution is 1-3 mol / L.

[0017] Preferably, the immersion time in step (3) is 3 to 6 hours; the freeze-drying temperature is -50 to -60°C, and the freezing time is 24 to 72 hours.

[0018] The present invention further provides a composite aerogel prepared by the above method.

[0019] The present invention also provides a composite aerogel prepared by the above method in adsorbing Cs in water. + , Sr 2+ application.

[0020] In a specific embodiment of the present invention, 20 mg of KMg@ZIF-8 / MoS2@SA aerogel was added to a system containing 20 mL of Cs + and Sr 2+ The concentration of the solution was 100 mg / L. After 24 h of shaking adsorption at 220 r / min in a constant temperature shaker, Cs in the wastewater was detected. + , Sr 2+ The removal rates can reach up to 98.9% and 99.8% respectively. After adsorption by the composite aerogel, Cs in wastewater can be purified by simple drying and separation. + , Sr 2+ purpose.

[0021] The present invention synthesizes MoS2 by a simple hydrothermal method, and then prepares MoS2@SA aerogel by cross-linking MoS2 and SA through calcium chloride. ZIF-8 is grown on the surface under the condition that Mo-S and C=O bonds gradually appear in its XPS spectrum. After confirming that the Zn-O bond is successfully constructed, potassium magnesium ferrocyanide is then grown on the surface to finally obtain KMg@ZIF-8 / MoS2@SA aerogel. It is used to selectively remove radioactive nuclides Cs and Sr elements in water bodies, and can be reused by simple drying and separation, which is energy-saving and environmentally friendly.

[0022] The beneficial effects of the present invention are: (1) The KMg@ZIF-8 / MoS2@SA aerogel provided by the present invention uses SA as a carrier, loads molybdenum disulfide, and grows ZIF-8, and finally grows Cs + , Sr 2+ Potassium magnesium ferrocyanide with selective adsorption performance, Mg 2+ Sr 2+ The selectivity is strong, achieving efficient purification of Cs and Sr ions. Compared with the traditional industrial separation method of Cs and Sr, it has low energy consumption, high selective separation efficiency, one-step solidification separation, no secondary pollution, and effectively avoids the shortcomings of redundant separation operations and large amount of waste liquid in traditional methods. The composite KMg@ZIF-8 / MoS2@SA aerogel can efficiently adsorb Cs in wastewater. + , Sr 2+ , the adsorption efficiency is as high as 98.9% and 99.8% respectively; (2) Using composite aerogel to adsorb Cs in water + , Sr 2+Afterwards, it can be effectively separated from the reaction system through simple drying and separation technology without secondary pollution; (3) The composite aerogel provided by the present invention has a strong effect on the Cs in pure water, tap water and seawater + , Sr 2+ All of them have good adsorption and removal effects. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 SEM image of KMg@ZIF-8 / MoS2@SA aerogel; Figure 2 XRD patterns of KMg@ZIF-8 / MoS2@SA aerogel and comparative materials; Figure 3 TGA graphs of KMg@ZIF-8 / MoS2@SA aerogel and comparative materials; Figure 4 This is the real water sample adsorption diagram of KMg@ZIF-8 / MoS2@SA aerogel; Figure 5 This is the recycling diagram of KMg@ZIF-8 / MoS2@SA aerogel. DETAILED DESCRIPTION

[0024] The present invention will be further described below in conjunction with the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solution of the present invention, and cannot be used to limit the protection scope of the present invention. Example 1

[0025] (1) MoS2 nanosheets were synthesized by a simple hydrothermal method. 2.498 g of ammonium molybdate ((NH4)6Mo7O2·4H2O) and 4.606 g of thiourea (CH4N2S) were dissolved in 70 mL of deionized water and stirred vigorously for 30 min. Then, the mixed solution was transferred to a 100 mL reactor and heated to 220 °C for 24 h. After cooling naturally to room temperature, the black product was rinsed several times with deionized water and ethanol and freeze-dried using a freeze dryer (-55 °C, 72 h) to obtain MoS2 nanosheets.

[0026] Take 50 mL of 20 mg / mL MoS2 dispersion, add 50 mL of 20 mg / mL sodium alginate solution, stir at 300 r / min for 10 min at 40°C, and ultrasonically react for 30 min. The obtained product is freeze-dried (-55°C, 24 h) and then taken out. 0.1 mol / L calcium chloride solution is added for cross-linking. After alternate washing with ethanol and pure water, it is freeze-dried (-55°C, 72 h) to obtain MoS2@SA aerogel. (2) The MoS2@SA aerogel was taken out and immersed in 0.432 g zinc acetate dihydrate dissolved in 20 mL aqueous solution for 3 h, and then immersed in 1.324 g 2-methylimidazole dissolved in 20 mL aqueous solution for 3 h, and then grown and freeze-dried (-55°C, 72 h). ZIF-8 / MoS2@SA aerogel was obtained.

[0027] (3) Take ZIF-8 / MoS2@SA aerogel and soak it in 4.2239 g potassium ferrocyanide dissolved in 20 mL aqueous solution (to ensure the concentration of the prepared solution is 0.5 mol / L) for 3 h, and then soak it in 2.033 g magnesium chloride dissolved in 20 mL aqueous solution for 3 h for growth. Then freeze-dry (-55 °C, 72 h) to obtain KMg@ZIF-8 / MoS2@SA aerogel.

[0028] Take 20 mg of the composite aerogel prepared in Example 1 and add it into a system with 20 mL of Cs + , Sr 2+ The concentration of 100 mg / L solution was placed in a constant temperature shaker at 220 r / min for 24 h to detect Cs in the wastewater. + , Sr 2+ The removal rates can reach 98.9% and 99.8% respectively. After adsorption, the composite aerogel can be separated by simple drying to achieve the adsorption of Cs in water. + , Sr 2+ purpose. Example 2

[0029] (1) As in Example 1, MoS2 nanosheets were synthesized by a simple hydrothermal method. 25 mL of 20 mg / mL MoS2 dispersion was added to 25 mL of 20 mg / mL sodium alginate solution of equal mass, stirred at 300 r / min for 10 min at 40°C, and ultrasonically reacted for 30 min. The obtained product was freeze-dried (-55°C, 24 h) and then taken out. 0.5 mol / L calcium chloride solution was added for cross-linking, and then alternately washed with ethanol and pure water and freeze-dried (-55°C, 72 h) to obtain MoS2@SA aerogel. (2) The MoS2@SA aerogel was taken out and immersed in 0.216 g zinc acetate dihydrate dissolved in 10 mL aqueous solution for 3 h, and then immersed in 0.662 g 2-methylimidazole dissolved in 10 mL aqueous solution for 3 h for growth, and freeze-dried (-55°C, 72 h) to obtain ZIF-8 / MoS2@SA aerogel.

[0030] (3) Take ZIF-8 / MoS2@SA aerogel and soak it in 4.2239 g potassium ferrocyanide dissolved in 20 mL aqueous solution (to ensure the concentration of the prepared solution is 0.5 mol / L) for 3 h, and then soak it in 2.033 g magnesium chloride dissolved in 20 mL aqueous solution for 3 h for growth. Then freeze-dry (-55 °C, 72 h) to obtain KMg@ZIF-8 / MoS2@SA aerogel.

[0031] Take 20 mg of the composite aerogel prepared in Example 2 and add it into a system with 20 mL of Cs + , Sr 2+ The concentration of 100 mg / mL solution was placed in a constant temperature shaker at 220 r / min for 24 h to detect Cs in the wastewater. + , Sr 2+ The removal rates can reach 95.1% and 96.7% respectively. Example 3

[0032] (1) As in Example 1, MoS2 nanosheets were synthesized by a simple hydrothermal method. 50 mL of 10 mg / mL MoS2 dispersion was added to 50 mL of 10 mg / mL sodium alginate solution, stirred at 40°C and 300 r / min for 10 min, and ultrasonically reacted for 30 min. The obtained product was freeze-dried (-55°C, 24 h) and then taken out. 0.1 mol / L calcium chloride solution was added for cross-linking, and then alternately washed with ethanol and pure water and freeze-dried (-55°C, 72 h) to obtain MoS2@SA aerogel. (2) The MoS2@SA aerogel was taken out and immersed in 0.864 g zinc acetate dihydrate dissolved in 40 mL aqueous solution for 3 h, and then immersed in 2.648 g 2-methylimidazole dissolved in 40 mL aqueous solution for 3 h, and then grown and freeze-dried (-55°C, 72 h). ZIF-8 / MoS2@SA aerogel was obtained.

[0033] (3) Take ZIF-8 / MoS2@SA aerogel and soak it in 4.2239 g potassium ferrocyanide (0.01 mol) dissolved in 10 mL aqueous solution (to ensure the concentration of the prepared solution is 1 mol / L) for 3 h, and then soak it in 2.033 g magnesium chloride (0.02 mol) dissolved in 10 mL aqueous solution for 3 h for growth. Then freeze-dry (-55 °C, 72 h) to obtain KMg@ZIF-8 / MoS2@SA aerogel.

[0034] Take 20 mg of the composite aerogel prepared in Example 3 and add it into a system with 20 mL of Cs + , Sr 2+The concentration of 100 mg / mL solution was placed in a constant temperature shaker at 220 r / min for 24 h to detect Cs in the wastewater. + , Sr 2+ The removal rates can reach 92.8% and 94.4%.

[0035] Comparative Example 1: MoS2@SA aerogel was prepared in the same manner as in Example 1. + , Sr 2+ The removal rates can reach 72.8% and 53.7% respectively.

[0036] Comparative Example 2: The same method as in Example 1 was used to prepare ZIF-8 / MoS2@SA aerogel. + , Sr 2+ The removal rates can reach 81.3% and 68.7% respectively.

[0037] Comparative Example 3: The difference from Example 1 is that in step (3), ferric chloride is used instead of magnesium chloride, and the concentration of the ferric chloride solution is 2 mol / L, thereby obtaining KFe@ZIF-8 / MoS2@SA aerogel. + , Sr 2+ The removal rates were 92.8% and 70.2% respectively.

[0038] The KMg@ZIF-8 / MoS2@SA aerogel prepared in Example 1 was characterized and analyzed as follows: Figure 1 This is the SEM image of KMg@ZIF-8 / MoS2@SA aerogel. The material was characterized by a SU8020 scanning electron microscope from Hitachi, Japan. Sample preparation: Weigh 5 mg of the sample and disperse it in 10 mL of anhydrous ethanol, ultrasonically treat it for 0.5 h, and after drying, stick the sample on a copper plate with conductive glue. After gold spraying, measure it and analyze the surface micromorphology of the material. The flower-like layered structure of MoS2 can be observed, and there are angular spherical particles on the sheet that clearly conform to the characteristics of ZIF-8, which not only expands the specific surface area of ​​the adsorbent, but also brings many functional groups and multiple adsorption sites, providing a basis for the selective adsorption of heavy metals by aerogels.

[0039] Figure 2The XRD diagram of KMg@ZIF-8 / MoS2@SA aerogel and comparative materials. The DX-2700 X-ray diffractometer of Shanghai Precision Instrument Co., Ltd. was used. Sample preparation: Take an appropriate amount of sample for slice preparation, measure under the conditions of Cu target, working voltage 35kV, current 25 mA, scanning step of 0.02°, scanning range 5°~80°, collect data every 0.5 seconds, and analyze the crystal structure of the material. It can be seen from the figure that KMg@ZIF-8 / MoS2@SA aerogel has obvious characteristic peaks at 2θ=14.9°, 15.5°, 17.6°, 24.9°, 35.8°, 44.7° and 51.3°, indicating that potassium magnesium ferrocyanide has been successfully grown on the surface of ZIF-8 / MoS2@SA aerogel, and it is consistent with the diffraction peak information in the literature.

[0040] Figure 3 The TGA graph of KMg@ZIF-8 / MoS2@SA aerogel and comparative materials. The TG-209-F3 thermogravimeter of NETZSCH, Germany was used. Sample preparation: Take an appropriate amount of sample (2-3 mg) and place it in the autosampler tray. Heat it at a rate of 10℃ / min until 800℃ in an air atmosphere, collect data, and analyze the high temperature resistance of the material. It can be seen from the figure that the mass reduction of KMg@ZIF-8 / MoS2@SA aerogel can be divided into three stages. The first stage is the slight mass loss caused by the evaporation and removal of water or residual methanol adsorbed in the cavity or surface of the adsorbent of the material itself; the faster weight loss in the second stage is caused by the collapse and thermal decomposition of the adsorbent material structure; the third stage is caused by further decomposition of the structure in the material. After the three-stage mass loss of KMg@ZIF-8 / MoS2@SA aerogel at 800℃, the remaining mass is still as high as 71.4701% of the original mass, showing good high temperature resistance.

[0041] Figure 4 Figure 2 is the real water sample adsorption diagram of KMg@ZIF-8 / MoS2@SA aerogel. The flame atomic absorption spectrometer of Jinan Jiedao Analytical Instrument Co., Ltd. was used. The actual water sample of the present invention was collected from the Yellow Sea. Sample preparation: To prepare the adsorption solution, the actual water sample was mixed with Cs + , Sr 2+ The solutions were mixed to reach 100 mg / L Cs at pH 6 and 293 K. + , Sr 2+ Concentration. Take the sample supernatant after adsorption and filter it using a 0.22 µm filter membrane, dilute it proportionally within 0~10 mg / L and then place it into the instrument for testing. Figure 4 It can be seen that the aerogel has a strong affinity for Cs in different water samples. + , Sr 2+The adsorption capacity of pure water>tap water>Yellow Sea water is the same as that of tap water. The reason is that there are many common positively charged metal ions in the tap water environment, such as K + , Ca 2+ 、Na + Mg 2+ The ionic radius of these ions is small, which makes it easy for the adsorbent to undergo ion exchange reactions and occupy adsorption sites, resulting in a decrease in its adsorption efficiency in tap water. In seawater, there are not only more types and numbers of positively charged metal ions, but also the pH is often kept at an alkaline level, which makes KMg@ZIF-8 / MoS2@SA aerogel more efficient in adsorbing Cs + , Sr 2 + When there is OH - precipitation, thus affecting the adsorption efficiency of aerogel.

[0042] Figure 5 Figure 2 shows the recycling of KMg@ZIF-8 / MoS2@SA aerogel. The flame atomic absorption spectrometer of Jinan Jiedao Analytical Instrument Co., Ltd. was used. Sample preparation: 20 mg of KMg@ZIF-8 / MoS2@SA aerogel was added to a solution containing 100 mg / L Cs + , Sr 2+ The solution was placed in a conical flask for 24 h. The aerogels were then eluted with 20 mL of 1 mol / L hydrochloric acid to study their cycling performance. The eluted KMg@ZIF-8 / MoS2@SA aerogels were dried in an oven for 24 h and then used again for Cs + , Sr 2+ The solution was used for adsorption experiment. The process was repeated five times, and the supernatant of the sample after adsorption was taken and filtered using a 0.22 µm filter membrane, and then diluted in proportion to 0-10 mg / L and placed in the instrument for testing. Figure 5 It can be seen that KMg@ZIF-8 / MoS2@SA aerogel still maintains excellent adsorption capacity (Cs + Reaching 48.19 mg / g, Sr 2+ Reach 85.21 mg / g), Cs + , Sr 2+ The adsorption efficiency remains above 90%, proving that KMg@ZIF-8 / MoS2@SA aerogel has good recycling ability.

[0043] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the technical principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for adsorbing Cs in water + , Sr 2+ A method for preparing a composite aerogel, characterized in that: The steps include: (1) The MoS2 dispersion and the sodium alginate solution are uniformly mixed to obtain a mixed solution, the mixed solution is freeze-dried and then taken out, a calcium chloride solution is added for cross-linking reaction, and the MoS2@SA aerogel is obtained after washing and drying; (2) The MoS2@SA aerogel is sequentially immersed in a soluble zinc salt aqueous solution and a 2-methylimidazole aqueous solution for a growth cycle, and then freeze-dried; after being taken out, the growth cycle is repeated to obtain ZIF-8 / MoS2@SA aerogel; (3) The ZIF-8 / MoS2@SA aerogel was immersed in an aqueous solution of potassium ferrocyanide and an aqueous solution of magnesium chloride in turn for full reaction, and then freeze-dried to obtain KMg@ZIF-8 / MoS2@SA aerogel.

2. The adsorption of Cs in water according to claim 1 + , Sr 2+ A method for preparing a composite aerogel, characterized in that: The mass ratio of MoS2 and sodium alginate in step (1) is 1:1, and the concentration of sodium alginate in the mixed solution is 5-10 mg / mL; and / or the concentration of the calcium chloride solution is 0.1-1 mol / L.

3. The adsorption of Cs in water according to claim 1 + , Sr 2+ A method for preparing a composite aerogel, characterized in that: The MoS2 described in step (1) is MoS2 nanosheets, which are prepared by the following method: dissolving or dispersing ammonium molybdate and thiourea in water, stirring and mixing evenly, hydrothermally reacting at 180-220°C for 24-48 hours, naturally cooling to room temperature, washing, and freeze-drying to obtain MoS2 nanosheets; wherein the molar ratio of thiourea in molybdenum ions of ammonium molybdate is 1:4-5.

4. The adsorption of Cs in water according to claim 1 + , Sr 2+ A method for preparing a composite aerogel, characterized in that: The molar ratio of the soluble zinc salt to 2-methylimidazole in step (2) is 1:8-9; the concentration of the soluble zinc salt aqueous solution is 0.09-0.1 mol / L; and the volume ratio of the soluble zinc salt aqueous solution to the 2-methylimidazole aqueous solution is 1:

1.

5. The method for adsorbing Cs in water according to claim 1 + , Sr 2+ A method for preparing a composite aerogel, characterized in that: The concentration of the potassium ferrocyanide aqueous solution in step (3) is 0.5-1.5 mol / L; the concentration of the magnesium chloride aqueous solution is 1-3 mol / L.

6. The method for adsorbing Cs in water according to claim 1 + , Sr 2+ A method for preparing a composite aerogel, characterized in that: The immersion time in step (2) is 3 to 6 hours; the total number of repeated growth cycles is more than three times; and / or the immersion time in step (3) is 3 to 6 hours.

7. The method for adsorbing Cs in water according to claim 1. + , Sr 2+ A method for preparing a composite aerogel, characterized in that: The freeze-drying temperature is -50 to -60°C, and the freezing time is 24 to 72 hours.

8. The composite aerogel prepared by the method according to any one of claims 1 to 7.

9. The composite aerogel according to claim 8 absorbs Cs in water + , Sr 2+ Application in.

Citation Information

Patent Citations

  • Ternary composite aerogel as well as preparation method and application thereof

    CN111939878A

  • ZIF-67 / PAM / CSA composite aerogel as well as preparation method and application thereof

    CN116459804A

  • Aerogel type MoS2 composite adsorbent, preparation method thereof and application of aerogel type MoS2 composite adsorbent in wastewater treatment

    CN116618028A

  • Nanometer defect molybdenum disulfide / viscose aerogel adsorption material as well as preparation method and application thereof

    CN116966882A

  • Composite aerogel for adsorbing Cu in water and preparation method thereof

    CN117718018A